Food safety in milk markets of smallholder farmers in Tanzania: A case of peri-urban wards in Temeke Municipality - Kilango, K. (Sokoine University of Agriculture, 2011)
The present study was carried out to establish food safety status of milk marketed by smallholder farmers in peri-urban wards of Temeke Municipality, Dar es salaam Tanzania between January 2010 to March 2010. A total of 69, 7 and 44 milk samples respectively from farmers, milk vendors and milk kiosks were collected from four randomly selected wards to assess presence of toxin producing staphylococcus aureus. At randomly selected milk selling shops, 120 consumers were interviewed on their perception regarding safety of milk. Standard methods were used to isolate S. aureus in milk samples. Data were analyzed using SPSS version 12.0. About 1792 litres (90%CI: 1337-2358) of milk are sold everyday in Temeke municipality peri-urban wards kiosks and out of this amount, 407 litres (90%CI: 119-799) was found to be contaminated with S. aureus. The probability of purchasing contaminated milk was therefore 0.227 (90%CI: 0.062-0.436). Every day, 953 (90%CI: 718-1,249) people purchase milk from kiosks in peri-urban Temeke, and among them, 217 (90%CI: 62-427) people were estimated to purchase contaminated milk. Milk quality as defined by Total Bacterial Count (TBC) along the chain was also determined and found to be an average of 2.8 x 106 ± 9.8 x 105 cfu at producer level, 3.4 x 107 ± 2.6 x 107 cfu at vendor’s level and 4.8 x 107 ± 3.3 x 107 cfu at kiosk level. TBC values for kiosk milk served hot was also determined and found to be an average of 3.7 x 105 ± 2.3 x 105 cfu. Other organisms isolated in the milk samples include Bacillus spp, Escherichia coli, Proteus spp, Enterobacteria spp, Corrynebacterium spp and Micrococcus spp. Consumers knowledge on health risks associated with milk consumption was high (71.67%) and there was no significant difference on the level of awareness among consumers in the sample wards (P>0.05).